Corporate asset purchases and sales: Theory and evidence☆ - WARUSAWITHARANA, M (Journal of Financial Economics, 2008)
Purchases and sales of operating assets by firms generated $162 billion for shareholders over the past 20 years. This contrasts sharply with the evidence on mergers. This paper characterizes the behavior of value-maximizing firms, which could grow organically, purchase existing assets, or sell assets. The approach yields an endogenous selection model that links asset purchases and sales to fundamental properties of the firm. Empirical tests confirm the predictions of the model. In particular, return on assets and size strongly predict when firms purchase or sell assets, and the transaction size covaries with the value of capital employed by the firm. These findings indicate that corporate asset purchases and sales are consistent with efficient investment decisions.